Cerebellar contributions to biological motion perception in autism and typical development. Issue 4 (2nd February 2017) - Jack, Allison; Keifer, Cara M.; Pelphrey, Kevin A.
Abstract: Growing evidence suggests that posterior cerebellar lobe contributes to social perception in healthy adults. However, they know little about how this process varies across age and with development. Using cross‐sectional fMRI data, they examined cerebellar response to biological (BIO) versus scrambled (SCRAM) motion within typically developing (TD) and autism spectrum disorder (ASD) samples (age 4–30 years old), characterizing cerebellar response and BIO > SCRAM‐selective effective connectivity, as well as associations with age and social ability. TD individuals recruited regions throughout cerebellar posterior lobe during BIO > SCRAM, especially bilateral lobule VI, and demonstrated connectivity with right posterior superior temporal sulcus (RpSTS) in left VI, Crus I/II, and VIIIb. ASD individuals showed BIO > SCRAM activity in left VI and left Crus I/II, and bilateral connectivity with RpSTS in Crus I/II and VIIIb/IX. No between‐group differences emerged in well‐matched subsamples. Among TD individuals, older age predicted greater BIO > SCRAM response in left VIIb and left VIIIa/b, but reduced connectivity between RpSTS and widespread regions of the right cerebellum. In ASD, older age predicted greater response in left Crus I and bilateral Crus II, but decreased effective connectivity with RpSTS in bilateral Crus I/II. In ASD, increased BIO > SCRAM signal in left VI/Crus I and right Crus II, VIIb, and dentate predicted lower social symptomaticity; increased effective connectivity with RpSTS in right Crus I/II and bilateral VI and I–V predicted greater symptomaticity. These data suggest that posterior cerebellum contributes to the neurodevelopment of social perception in both basic and clinical populations. Hum Brain Mapp 38:1914–1932, 2017 . ©2017 Wiley Periodicals, Inc.